2013
DOI: 10.1007/s00267-013-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Exploitation Management Under Land Subsidence Constraint: Empirical Evidence from the Hangzhou–Jiaxing–Huzhou Plain, China

Abstract: Land subsidence caused by extensive groundwater pumping has become a factor which cannot be ignored in the sustainable exploitation of groundwater resources. The Hangzhou-Jiaxing-Huzhou Plain is one of the locations with China's most severe land subsidence problems; the region has experienced dramatic land subsidence since the 1960s. Historical records of groundwater extraction, hydraulic head, and land subsidence show the latter to be the result of continual and excessive extraction of groundwater from deep c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Due to such large amounts of historical withdrawal and long-term groundwater exploitation, both groundwater level declines and land subsidence were the result. Cao et al [25] reported that 66% of the Beijing plain has been affected by more than 50 mm land subsidence, covering an area of 4.2 × 10 3 km 2 . Ye et al [26] have also provided evidence showing the overall land-subsidence affected areas in China have exceeded 90,000 km 2 by 2015.…”
Section: The Groundwater Perspectivementioning
confidence: 99%
“…Due to such large amounts of historical withdrawal and long-term groundwater exploitation, both groundwater level declines and land subsidence were the result. Cao et al [25] reported that 66% of the Beijing plain has been affected by more than 50 mm land subsidence, covering an area of 4.2 × 10 3 km 2 . Ye et al [26] have also provided evidence showing the overall land-subsidence affected areas in China have exceeded 90,000 km 2 by 2015.…”
Section: The Groundwater Perspectivementioning
confidence: 99%
“…Documentation of the subsidence of Venice, Italy [ Gambolati and Freeze , ] served as a wake‐up call and presented a quantitative simulation analysis of how coupled hydraulic and hydromechanical behavior can have dire consequences. Land subsidence has been documented in regions including Santa Clara Valley, California, Las Vegas, Nevada, Bankok, Thailand, the Mekong Delta, and the Yangtze Delta [ Cao et al ., ]. Predictive models exist and are being used, as demonstrated by Teatini et al .…”
Section: Six Dimensions Of Groundwater Vulnerabilitymentioning
confidence: 99%
“…Additionally, 66% of the Beijing plain has been affected by land subsidence (>50 mm) with a maximum subsidence of 1.23 m [10]. It is now known from the records of groundwater extraction, hydraulic head, and land subsidence, that land subsidence is the result of continual and excessive extraction of groundwater from deep confined aquifers (e.g., see Reference [11,12]).…”
Section: Introductionmentioning
confidence: 99%